Evaluation of potential drug-drug interactions with medical cannabis - Jessie Jia Yi Ho; Chenyi Goh; Caitlin Shen Ai Leong; Khuen Yen Ng; Athirah Bakhtiar (Wiley, 2024)
Abstract Cannabis-drug interactions have caused significant concerns, mainly due to their role in the cytochrome P450 (CYP) enzyme‐mediated metabolic pathway of numerous medications. A systematic review was conducted to gain an overview of the potential interactions of cannabis with different drug classes by extracting pertinent information from published study data. From the inception of the study to October 1, 2023, we performed a systematic search of PubMed, Scopus, clinicaltrials.gov, and Web of Science. We included 54 out of 464 articles, and a total of 20 drug classes were identified to have interactions with medicinal cannabis. The cannabis-drug interactions were assessed and classified according to their probability and severity. The analysis revealed that antiepileptics had the most evidence of interaction with cannabis, followed by clobazam (CLB), warfarin, and tacrolimus. Generally, cannabis-drug interactions result in pharmacokinetic (PK) or pharmacodynamic (PD) changes. Therefore, careful monitoring should be performed to detect any unusual elevations in plasma levels. In addition, dose titrations or treatment withdrawal could help mitigate the adverse effects attributed to cannabis-drug interactions. Nevertheless, novel drugs are constantly emerging, and more research is needed to further identify potential interactions with cannabis.